1990
DOI: 10.1007/bf01073938
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of enterohepatic circulation of cefixime in rat by fast inverse Laplace transform (FILT)

Abstract: The enterohepatic circulation of cefixime in rat was evaluated by a nonlinear least square analysis program, MULTI(FILT), into which the fast inverse Laplace transform (FILT) was incorporated. The plasma time course in the bile duct-cannulated rat exhibited a biexponential curve after the rapid iv administration of cefixime. Several pharmacokinetic models for the enterohepatic circulation were constructed based on the recirculatory concept and the Laplace-transformed equations corresponding to these models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…We can apply the recirculatory concept (Yamaoka et al 1990) in the present model. The extraction ratio throughout the single-pass (one-cycle) process between compartment 1 and compartment B can be estimated by equation 10.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…We can apply the recirculatory concept (Yamaoka et al 1990) in the present model. The extraction ratio throughout the single-pass (one-cycle) process between compartment 1 and compartment B can be estimated by equation 10.…”
Section: Theorymentioning
confidence: 99%
“…Several pharmacokinetic models have been tried to explain the enterohepatic circulation of a drug ; the most popular are compartment models with a lag time (sometimes called gap time), from bile compartment to plasma compartment (Dahlstrom & Paalzow 1978 ;Pedersen & Miller 1980a, b ;Steimer et al 1982 ;Colburn 1984 ;Miller 1984 ;Shepard et al 1985Shepard et al , 1989Plusquellec & Houin 1992, 1995Hoglund & Ohlin 1993 ;Khalil et al 1993 ;Plusquellec et al 1998 ;Funaki 1999). To simulate the secondary peaks in a plasma concentration pro® le due to enterohepatic circulation, the recirculatory concept, in which enterohepatic circulation is regarded as a recirculation process of drug molecules between the bile and the plasma compartments, has also been proposed (Yamaoka et al 1990 ;Fukuyama et al 1994 ;Yasui et al 1994Yasui et al , 1996. However, these methods have only been used to explain the data in a single dosing study, and there have been few reports on pharmacokinetic models applied to data analysis in a repeated dosing study.…”
Section: Introductionmentioning
confidence: 99%
“…Recirculatory Model for EHC of Drug and MetabolitesA recirculatory model was introduced for the understanding of the EHC of a drug, [21][22][23] and it was shown that the proposed concept included not only simple EHC models [24][25][26] but the EHC models extended by Shepard et al 27,28 and Ribera et al 29 Figure 1 represents an expanded X Abstract published in Advance ACS Abstracts, April 1, 1996.…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…21 Considering the difficulty in the Laplace inversion of the image equations, MULTI(FILT) incorporating a fast inverse Laplace transform (FILT) was adopted to kinetically investigate EHC. 22,23 It is attempted in the present investigation to simply evaluate the stereoselective EHC and the synchronous chiral inversion of ketoprofen enantiomers by means of moment analysis.…”
Section: Introductionmentioning
confidence: 99%
“…1,[3][4][5][6][7][8] (14) where F a is absorption ratio from intestinal tract into the portal system and D p.o. is orally administered drug amount and Q p is blood flow rate of portal vein, respectively.…”
Section: Sysmentioning
confidence: 99%